North station - Bae, Su a 1965- (Open Letter, 2017)
"A writer struggles to come to terms with the death of her beloved mentor; the staging of an experimental play goes awry; time freezes for two lovers on a platform, waiting for the train that will take one of them away; a woman living in a foreign country discovers she has been issued the wrong ID. Emotionally haunting and intellectually stimulating, the seven stories in North Station represent the range and power of Bae Suah's distinctive voice and style, which delights in digressions, multiple storylines, and sudden ruptures of societal norms. Heavily influenced by the German authors she's read and translated, Bae's stories combine elements of Korean and European storytelling in a way that's unforgettable and mesmerizing"...